Indirect costs associated with skin infectious disease in children: a systematic review - Irene Lizano-Díez; Jesús Naharro; Ilonka Zsolt (BMC, 2021)
Abstract Background There are limited data in the literature on the indirect costs associated with skin and soft tissue infections (SSTIs) in the pediatric population. This study aimed to conduct a systematic review of the indirect costs associated with SSTIs in children. Methods The search was conducted in PubMed, SCOPUS, and Web of Science up to January 2020. Thirteen search strategies were designed combining MeSH terms and free terms. SSTIs were defined as bacterial or viral infections, dermatomycoses, and parasitic infestations. Only primary studies were included. All analyzed costs were converted to 2020 Euros. Results Thirteen of the identified publications presented indirect costs of SSTIs in children and were conducted in Argentina, Australia, Brazil, Hungary, New Zealand, Poland, Spain, Taiwan, and the USA. Nine studies described indirect costs associated with infection of Varicella-zoster virus: lost workdays by outpatient caregivers ranged from 0.27 to 7.8, and up to 6.14 if caring for inpatients; total productivity losses ranged from €1.16 to €257.46 per patient. Three studies reported indirect costs associated with acute bacterial SSTIs (community-associated methicillin-resistant Staphylococcus aureus) in children: total productivity losses ranged from €1,814.39 to €8,224.06 per patient, based on impetigo, cellulitis, and folliculitis. One study of parasitic infestations (Pediculus humanus capitis) reported total indirect costs per patient of €68.57 (formal care) plus €21.41 due to time lost by parents in purchasing treatment. Conclusions The economic burden of SSTIs is highly relevant but underestimated due to the lack of studies reporting indirect costs. Further cost studies will allow a better understanding of the magnitude of the financial burden of the disease.